TNFSF14 (LIGHT) Exhibits Inflammatory Activities in Lung Fibroblasts Complementary to IL-13 and TGF-β - da Silva Antunes, Ricardo; Mehta, Amit K.; Madge, Lisa; Tocker, Joel; Croft, Michael (Frontiers in Immunology, 2018)
The cytokine TNFSF14 (LIGHT) has been shown in mouse models to be important for development of lung tissue remodeling that is characteristic of asthma, IPF, and SSc. However, its cellular targets are not fully delineated. In the present report, we show that LTβR and HVEM, the receptors for LIGHT, are constitutively expressed in primary human lung fibroblasts (HLFs). We asked whether LIGHT could promote inflammatory and remodeling-relevant activity in HLFs and how this was similar to, or distinct from, IL-13 or TGF-β, two cytokines strongly implicated in the pathogenesis of asthma, IPF, and SSc. Accumulation of myofibroblasts expressing alpha smooth muscle actin is a feature of lung inflammatory diseases. LIGHT promoted cell cycle progression and proliferation of HLFs, but not alpha smooth muscle actin expression. In contrast, TGF-β upregulated alpha smooth muscle actin but did not drive their proliferation. LIGHT also increased the gene or protein expression of a number of pro-inflammatory mediators, including ICAM-1 and VCAM-1, IL-6 and GM-CSF, the chemokines CCL5 and 20, and CXCL5, 11, and 12, and lung remodeling-associated proteinases MMP-9 and ADAM8. These were dependent on LTβR but not HVEM. LIGHT displayed overlapping and synergistic activities with IL-13 for a number of the activities, but LIGHT additionally enhanced the gene expression of several molecules, including the innate cytokines IL-33 and TSLP, which were not upregulated by IL-13. Our results highlight the varied and pleiotropic effects of LIGHT in human lung fibroblasts. LIGHT might then be a therapeutic target for modulation of inflammation and remodeling associated with asthma and other similar diseases of the lung that involve fibroblasts.